2014
DOI: 10.1111/acem.12396
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Yields, Charges, and Radiation Dose of Chest Imaging in Blunt Trauma Evaluations

Abstract: Background: Chest radiography (CXR) is the most common imaging in adult blunt trauma patient evaluation. Knowledge of the yields, attendant costs, and radiation doses delivered may guide effective chest imaging utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 26 publications
1
30
1
Order By: Relevance
“…Even though CXR misses most SF, our findings do not necessarily advocate for increased chest CT utilization in blunt trauma-at least not for the purposes of solely identifying SF. Chest CT is much more expensive than CXR and delivers nearly a thousandfold the effective radiation dose to radiosensitive organs, with quantifiable resultant higher cancer risk [7,17]. SF diagnosis will continue to rise with increasing chest CT use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though CXR misses most SF, our findings do not necessarily advocate for increased chest CT utilization in blunt trauma-at least not for the purposes of solely identifying SF. Chest CT is much more expensive than CXR and delivers nearly a thousandfold the effective radiation dose to radiosensitive organs, with quantifiable resultant higher cancer risk [7,17]. SF diagnosis will continue to rise with increasing chest CT use.…”
Section: Discussionmentioning
confidence: 99%
“…Widely available, rapid CT has transformed diagnostic trauma evaluation with many centres adopting routine head-to-pelvis CT (pan-scan) for victims of major trauma [5][6][7][8]. Computed tomography has replaced X-ray as the imaging modality of choice for evaluation of patients with trauma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 The study found that only 6.9% (6.2%-7.7%) of chest CTs found a clinically significant injury. After calculating the effective dose of chest imaging, the authors determined that only one significant injury was found per 129 (101.4-217.4) mSv of radiation, suggesting that a substantial number of trauma investigations find no clinically significant injury.…”
Section: Discussionmentioning
confidence: 91%
“…For instance, when performing after a normal chest radiograph, CT diagnoses only one major injury for every 67 studies (5). Rodriguez et al have designed a cohesive summary algorithm so-named NEXUS Chest X-ray, which consists of seven criteria (age >60 years; rapid deceleration mechanism; chest pain; intoxication; altered mental status; distracting painful injury; and chest wall tenderness) and exhibits a sensitivity of 99.0% [95% confidence interval (CI), 98.2-99.4%) and a specificity of 13.3% (95% CI, 12.6-14.0%) for detecting clinically significant injuries, reinforcing the efficacy of X-ray chest imaging in the evaluation of all blunt trauma patients (6).…”
Section: Review Articlementioning
confidence: 99%